2010
DOI: 10.1161/atvbaha.110.210237
|View full text |Cite
|
Sign up to set email alerts
|

Group X Secretory Phospholipase A 2 Negatively Regulates ABCA1 and ABCG1 Expression and Cholesterol Efflux in Macrophages

Abstract: Objectives Group X secretory phospholipase A2 (GX sPLA2) potently hydrolyzes plasma membranes to generate lysophospholipids and free fatty acids and has been implicated in inflammatory diseases including atherosclerosis. Here we identify a novel role for GX sPLA2 in modulating ABCA1 and ABCG1 expression and hence macrophage cholesterol efflux. Methods and Results Overexpression or exogenous addition of GX sPLA2 significantly reduced ABCA1 and ABCG1 expression in J774 macrophage-like cells, whereas GX sPLA2 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
33
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 35 publications
7
33
0
Order By: Relevance
“…We and others have reported that GX sPLA 2 potently releases arachidonic acid (AA) and thus enhances PGE2 production in multiple cell types (30,32,33). Here we show that increased GX sPLA 2 activity leads to enhanced PGE2 production in beta cells.…”
Section: Gx Spla 2 Deficiency Is Associated With Enhanced Glucosestimsupporting
confidence: 57%
See 2 more Smart Citations
“…We and others have reported that GX sPLA 2 potently releases arachidonic acid (AA) and thus enhances PGE2 production in multiple cell types (30,32,33). Here we show that increased GX sPLA 2 activity leads to enhanced PGE2 production in beta cells.…”
Section: Gx Spla 2 Deficiency Is Associated With Enhanced Glucosestimsupporting
confidence: 57%
“…7). We previously reported that GX sPLA 2 modulates cellular functions by negatively regulating LXR activity in macrophages, adrenal cells, and fat cells (30,31,43). The LXR target genes ABCA1 and ABCG1 play critical roles in maintaining beta cell function by regulating cellular cholesterol homeostasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Are Overexpressed-We previously reported that GX sPLA 2 inhibits LXR-mediated target gene activation through a mechanism that is dependent on its enzymatic activity (10). Therefore, we investigated whether proteolytic activation of GX sPLA 2 by furin or PCSK6 enhances GX sPLA 2 -dependent inhibition of LXR activation.…”
Section: Suppression Of Lxr Activation By Gx Spla 2 Is Enhanced When mentioning
confidence: 99%
“…We also determined that GX sPLA 2 suppresses LXR activation in macrophages, resulting in reduced expression of ATP-binding cassette transporters A1 (ABCA1) and G1 (ABCG1) (10). Consequently, macrophages from GX KO mice exhibit increased cellular cholesterol efflux and decreased cellular cholesterol content (10). GX sPLA 2 is expressed in adrenal cells, where it suppresses corticosteroid production through a mechanism that also appears to involve LXR.…”
mentioning
confidence: 99%